Types of synergy and economic value: The impact of acquisitions on merging and rival firms - Chatterjee, Sayan (Strategic Management Journal, 1986)
Abstract Acquisitions, in general, have been demonstrated to create economic value. The intuitive reason underlying this value creation stems either from an ability to reduce costs of the combined entity, an ability to charge higher prices, or both. Current research in the area attributes these abilities to an opportunity to utilize a specialized resource. Our focus in this study is to compare three broad classes of resources that contribute to the creation of value. Following the conventional wisdom, these resources are classified as cost of capital related (resulting in financial synergy), cost of production related (resulting in operational synergy), and price related (resulting in collusive synergy). Given the limitations of our sample and research design, we find that collusive synergy is, on average, associated with the highest value. Further, the resources behind financial synergy tend to create more value than the resources behind operational synergy.